1999
DOI: 10.1063/1.123232
|View full text |Cite
|
Sign up to set email alerts
|

A vertical injection blue light emitting diode in substrate separated InGaN heterostructures

Abstract: A vertical injection, light emitting InGaN quantum well diode has been demonstrated by separating the nitride heterostructure from its sapphire substrate by ultraviolet laser photoablation within a process scheme that allows transferring the devices to a host substrate. The incorporation of a dielectric multilayer stack to the device is shown to be a first practical step towards a resonant cavity light emitting diode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…The blue GaN-based LEDs and edge emitting LDs have been developed in recent years. The research interest has gradually shifted to the development and demonstration of GaN-based vertical cavity surface emitting lasers (VCSELs) [1][2][3][4] and resonant-cavity light-emitting diodes (RCLEDs) [5][6][7][8][9][10]. An important requirement for the operation of such devices is the need of high reflectance mirrors, usually in the form of distributed Bragg reflectors (DBRs).…”
Section: Introductionmentioning
confidence: 99%
“…The blue GaN-based LEDs and edge emitting LDs have been developed in recent years. The research interest has gradually shifted to the development and demonstration of GaN-based vertical cavity surface emitting lasers (VCSELs) [1][2][3][4] and resonant-cavity light-emitting diodes (RCLEDs) [5][6][7][8][9][10]. An important requirement for the operation of such devices is the need of high reflectance mirrors, usually in the form of distributed Bragg reflectors (DBRs).…”
Section: Introductionmentioning
confidence: 99%
“…Nakada et al reported that considerably higher output power was obtained from a GaInN LED after inserting a DBR between the LED structure and sapphire substrate [1]. Since thin-film laser lift-off (LLO) techniques have recently been developed [2][3][4], GaN-based LEDs fabricated on reflective-metal-mirrorcoated Si substrates by transferring the LED structures from sapphire substrates have been demonstrated [5]. In comparison with this, epitaxial DBR GaN-based LEDs on Si can be grown through one growth process, providing an advantage of a simple process.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, devices fabricated on an electrically and thermally conducting substrate by separating sapphire substrate, are most desirable. Recently, the Laser lift-off (LLO) technique has been used to fabricate the freestanding InGaN LEDs [1,2] and LDs [3] as well as the creation of GaN substrate.…”
mentioning
confidence: 99%